Green Economy and Islamic Economy: Towards Accelerating SDGs - Hidayati, Yulia Eva; Addainuri, Muhammad Isbad; Fahrurrozi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
The conventional economic system has led to rapid global development, but there is a need to explore alternative approaches. This paper addresses the limited research on the integration of green and Islamic economics, focusing on their contribution to Sustainable Development Goals (SDGs) and intergenerational prosperity. Employing a qualitative research method, the study reveals that green and Islamic economies complement each other due to their shared objective of societal welfare across generations. Both perspectives view SDGs as initiatives that promote equality and sustainable use of natural resources. Achieving these goals requires substantial funding, which is where Islamic financial instruments come into play, providing essential support for financing SDG-related activities. This research highlights the synergy between these two economic models and their potential to drive long-term, equitable development.